Exploring the high abundance discrepancy in the planetary nebula IC 4663 - Mohery, M.; Ali, A.; Khames, Aya A.; Snaid, S.; Mindil, A. (Frontiers in Astronomy and Space Sciences, 2023)
This article presents an in-depth analysis of integral field unit spectroscopy performed on the Galactic planetary nebula (PN) IC 4663, with a primary focus on investigating its physical characteristics, chemical composition, and morphological properties. The examination involved the utilization of a series of emission-line maps representing various elements and ionization zones, allowing for a comprehensive assessment of morphological and ionization structure of IC 4663. The majority of these maps depict an overall elliptical shape, featuring a relatively faint core at the center. Emanating from this core are two distinct and illuminated lobes extending in opposite directions, forming a conspicuous double-lobed configuration. The chemical analysis conducted on IC 4663 has revealed that the PN is rich in both helium and nitrogen, characterized by an N/O ratio exceeding 0.5, classifying it as a Peimbert type I nebula. Furthermore, the presence of a notably intense He II emission line at λ4686, in conjunction with the existence of high-excitation lines within the nebular spectrum, indicate its classification as a high-excitation class nebula. The computation of O 2+ , N 2+ , and N 3+ through optical recombination lines has unveiled extreme abundance discrepancy factors, with values of 39.0 ± 6 for O 2+ and 37.0 ± 9 for N 2+ and N 3+ . These findings suggest the possibility that the central star of IC 4663 may be part of a binary system with a sub-stellar companion, potentially engaged in a common envelope interaction. Recent astrometric data derived from the Gaia mission further indicate a significant likelihood of interaction between the asymptotic giant branch halo of the PN and its surrounding interstellar medium, particularly in the southeast direction.